Systematic review of intra-abdominal and intrathoracic pressures initiated by the Valsalva manoeuvre during high-intensity resistance exercises - Blazek, Dusan; Stastny, Petr; Maszczyk, Adam; Krawczyk, Magdalena; Matykiewicz, Patryk; Petr, Miroslav (Biology of Sport, 2019)
The Valsalva manoeuvre, intra‑abdominal pressure (IAP) and intrathoracic pressure (ITP) play important roles in resistance training and common daily activities. The purpose of this review is to summarize the ITP and IAP responses to resistance exercises and to determine which exercises elicit the highest or lowest body pressure values under high-intensity resistance exercise. The PubMed, Scopus and Web of Science databases were searched until November 1, 2018. A combination of the following search terms was used: Valsalva manoeuvre, hold breath, controlled breathing, controlled breath, abdominal pressure, intrathoracic pressure AND weight training, resistance exercise, power lifting. The search process yielded 1125 studies, of which 16 were accepted according to the selection criteria and methodological quality. The highest IAP was recorded during squats (over 200 mmHg) followed by deadlift, slide row and leg press (161–176 mmHg), and the lowest IAP was found during bench press (79±44 mmHg). The highest ITP was elicited by the leg press, deadlift and box lift (105–130 mmHg), which were higher than during the bench press (95±37 mmHg) and slide row (88±32 mmHg). We recommend the bench press and slide row as exercises useful for beginners and individuals with hypertension. Untrained individuals should not use heavy squats, deadlift, box lift and clean exercises until they have undergone progressive adaptation for lifting high loads resulting in high IAP and ITP. The values of IAP and ITP during high-intensity exercise seem to be determined mutually by the position of the human body and the external load.